Mixing of porpoise ecotypes in southwestern UK waters revealed by genetic profiling. Issue 3 (1st March 2017) - Fontaine, Michaël C.; Thatcher, Oliver; Ray, Nicolas; Piry, Sylvain; Brownlow, Andrew; Davison, Nicholas J.; Jepson, Paul; Deaville, Rob; Goodman, Simon J.
Abstract : Contact zones between ecotypes are windows for understanding how species may react to climate changes. Here, we analysed the fine-scale genetic and morphological variation in harbour porpoises ( Phocoena phocoena ) around the UK by genotyping 591 stranded animals at nine microsatellite loci. The data were integrated with a prior study to map at high resolution the contact zone between two previously identified ecotypes meeting in the northern Bay of Biscay. Clustering and spatial analyses revealed that UK porpoises are derived from two genetic pools with porpoises from the southwestern UK being genetically differentiated, and having larger body sizes compared to those of other UK areas. Southwestern UK porpoises showed admixed ancestry between southern and northern ecotypes with a contact zone extending from the northern Bay of Biscay to the Celtic Sea and Channel. Around the UK, ancestry blends from one genetic group to the other along a southwest--northeast axis, correlating with body size variation, consistent with previously reported morphological differences between the two ecotypes. We also detected isolation by distance among juveniles but not in adults, suggesting that stranded juveniles display reduced intergenerational dispersal. The fine-scale structure of this admixture zone raises the question of how it will respond to future climate change and provides a reference point for further study.